PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN (Studi Pada PT. Tri Cahaya Purnama Semarang) - Prasto Aji Suryo, 14.05.51.0216; Kasmari, Kasmari (Students' Journal of Economic and Management, 2018)
This aim of this study is to know and analyze the influence of leadership, work environment, work stress to employees performance at PT. Tri Cahaya Prunama Semarang. The Method of taking data used in this study is primer data from form of questionnaires. Population of this research are employees from PT. Tri Cahaya Purnama around 500 people. The method of taking the sample is purposive sampling with amount of respondent is around 85 people. Hypothesis test in this research use multiple regression analysis. The result of multiple regression analysis is known that leadership, work environment have a positive influence to employees performance. While Work Stress did not have influence to employees performance. Keyword : Leadership, Work Environment, Work Stress and Employees Performance.